A systematic review of lateral wedge orthotics--how useful are they in the management of medial compartment osteoarthritis? - Reilly, K; Barker, K; Shamley, D (2006)
Studies on the use of lateral wedge orthotics in the conservative management of medial compartment osteoarthritis are widely quoted. This approach, however, does not consider the disruption of the interaction between lower limb and foot and ankle function that lateral wedges would produce. This comprehensive, systematic review was therefore undertaken to evaluate all available literature to determine whether evidence exists to support their use. MEDLINE, EMBASE, CINAHL, Allied and Complimentary Medicine, PubMed, EBSCO HOST and PEDro, Abstracts of Reviews of Effects in the National Electronic Library for Health for Cochrane Reviews and manual searching were used to identify studies. was searched for trials in progress. Data extraction was performed by the three authors using a paper data extraction form which was based on the CONSORT statement and Critical Skills Appraisal Programme (CASP) guidelines. Overall, the results of this review suggest that, based on current evidence there are no major or long-term beneficial effects with the use of lateral wedges.